Emerging medical therapies for non-alcoholic fatty liver disease and for alcoholic hepatitis - Wong, Vincent Wai-Sun; Singal, Ashwani K. (Translational Gastroenterology and Hepatology, 2019)
Non-alcoholic fatty liver disease (NAFLD) and alcoholic liver disease (ALD) are currently the two most common liver diseases in the world. Alcoholic hepatitis (AH), a unique clinical syndrome among ALD patients has high short-term mortality. Apart from controlling the risk factor for individual respective disease, there are no Food and Drug Administration (FDA) approved medical therapies for these diseases. Over the last 5–10 years, the field has extensively grown with many new targets being studied in randomized clinical trials for these diseases, with many of these drugs being tested in both the conditions. In this chapter, we will describe the novel therapeutic agents and current status of ongoing clinical trials with these agents for the treatment of NAFLD and/or AH.